2(2x-9)-5=2(x-5)-3

Simple and best practice solution for 2(2x-9)-5=2(x-5)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x-9)-5=2(x-5)-3 equation:


Simplifying
2(2x + -9) + -5 = 2(x + -5) + -3

Reorder the terms:
2(-9 + 2x) + -5 = 2(x + -5) + -3
(-9 * 2 + 2x * 2) + -5 = 2(x + -5) + -3
(-18 + 4x) + -5 = 2(x + -5) + -3

Reorder the terms:
-18 + -5 + 4x = 2(x + -5) + -3

Combine like terms: -18 + -5 = -23
-23 + 4x = 2(x + -5) + -3

Reorder the terms:
-23 + 4x = 2(-5 + x) + -3
-23 + 4x = (-5 * 2 + x * 2) + -3
-23 + 4x = (-10 + 2x) + -3

Reorder the terms:
-23 + 4x = -10 + -3 + 2x

Combine like terms: -10 + -3 = -13
-23 + 4x = -13 + 2x

Solving
-23 + 4x = -13 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-23 + 4x + -2x = -13 + 2x + -2x

Combine like terms: 4x + -2x = 2x
-23 + 2x = -13 + 2x + -2x

Combine like terms: 2x + -2x = 0
-23 + 2x = -13 + 0
-23 + 2x = -13

Add '23' to each side of the equation.
-23 + 23 + 2x = -13 + 23

Combine like terms: -23 + 23 = 0
0 + 2x = -13 + 23
2x = -13 + 23

Combine like terms: -13 + 23 = 10
2x = 10

Divide each side by '2'.
x = 5

Simplifying
x = 5

See similar equations:

| 25-12x=30 | | 7x-(2x+17)=18 | | 49=7/8(v) | | -7=-5a-2a | | 2x+11=-9x-18 | | 9(z-6)=4(z-4) | | 9(x+5)=9(x+10) | | t=3+14t-5t^2 | | h(t)=3+14t-5t^2 | | -2x+2=-1 | | 5s+2=5c-2 | | -5n+3=-22 | | 2x+13=-3x-20 | | -1/5x=-12 | | 5t-4=-14 | | (x*2)-9=x | | 8x+12=-6x-18 | | -6(m-23)=1 | | a+b=cfindb | | 8+5v=-8(-8v+8)+v | | 1/7-11=1/4x-14 | | 3.2+2.2x=3x | | x(2x-3)(4x+1)=0 | | 2x^2-2=45 | | -x-4.7=9 | | x/4=4/3 | | c=37+22h | | 12x-y=-10 | | 1/2r=3 | | c=22h+37 | | -36-8n=-3(3n+2)-5n | | f(x)=-3x^2-30x-82 |

Equations solver categories